PENGARUH SANKSI PERPAJAKAN DAN SOSIALISASI PERPAJAKAN TERHADAP MOTIVASI MEMBAYAR PAJAK BUMI BANGUNAN PERKOTAAN DAN PEDESAAN (PBB P2) (STUDI PADA WAJIB PAJAK DI KELURAHAN AIRLANGGA KOTA SURABAYA) - Damayanti, Gia Riessyta (Jurnal Mahasiswa Perpajakan, 2015)
Land and building tax are one of the taxes collected by central goverment. To support the policy of regional autonomy, then done the transfer tax management of the land and building urban and rural - act based on act no 28 year 2009 on a regional tax levies. This research explans by using quantitative approach. This research is spreading the questionnaire to 97 respondents taxes of the land and building taxpayers in Airlangga urban, Surabaya. Technique of Data analysis in this research uses descriptive analysis and multiple linear regression analysis to test hypothesis through the F test (simultaneous) and t test (partial). The result of this research indicates that all the hypothesis are accepted. Based on the results in this research that can be a significant influence together (simultaneously) sanctions of taxation and socialization of taxation variables on the motivation to pay taxes of the land and building tax urban and rulal. Partially known that sanction of taxation significantly affect the value of the regression coefficient of 0,628. While socialization of taxation has partially significant effect on the motivation to pay taxes of the land and building tax urban rural with a regression coefficient of 0,487. Keyword: Sanctions of taxation,the socialization of taxation, motivation to pay taxes of the land and buliding urban and rural.